Researching the future of purchasing and supply management: The purpose and potential of scenarios. Issue 3 (June 2020) - Knight, Louise; Meehan, Joanne; Tapinos, Efstathios; Menzies, Laura; Pfeiffer, Alexandra
Abstract: Drawing on prior research, the value of scenario planning as a methodology for researching the future of purchasing and supply management (PSM) is explored. Using three criteria of research quality – rigour, originality and significance – it is shown how developing scenarios and analysing their implications present new, important research opportunities for PSM academics, practitioners, and leaders of the profession. Researching the future of PSM supports the identification of uncertainties and anticipates change across many units and levels of analysis of interest to PSM scholars and practitioners, such as the profession/discipline, markets/sectors, or organisations. Scenarios are particularly effective for: considering how the complex interaction of macro-environmental factors affects the PSM context; avoiding incremental thinking; surfacing assumptions and revealing significant blind spots. PSM research using scenarios aligns with Corley and Gioia's (2011) call for prescience-oriented research in which academics aim for more impactful research, enhancing sense-giving potential and theoretical relevance to practice, to better perform their adaptive role in society. Highlights: Reviews approaches to research the future of purchasing & supply management. Highlights scenario planning and prescience-oriented research. Makes the case for developing scenarios in PSM research. Evaluates the potential of scenario-based research on the future of PSM (rigour, originality & significance).